On the Evolution of the γ/γ′ Lattice Misfit and TCP Phase Precipitation in a Highly Alloyed Single Crystalline Ni-Base Superalloy - Bandorf, Jakob; Kirzinger, Anna; Zenk, Christopher; Pang, H. T.; Rae, C. M.F.; Stone, H. J.; Neumeier, Steffen (Minerals, Metals and Materials Series, 2024)
Ni-base superalloysNi-base superalloys of the latest generation are prone to the formation of topologically close-packed (TCP) phases due to their high content of refractory elements. The quantitative correlation between the TCP phaseTCP phasesprecipitationPrecipitation, the evolution of the lattice parametersLattice parameter, and the γ/γ′ lattice misfitLattice misfit in a highly alloyed single crystalSingle crystal Ni-base superalloy Ni-base superalloySuperalloys is investigated here. Even in the standard heat-treated state TCP phasesTCP phases are found in the dendrite cores. With additional annealing at 1100 °C further TCP phaseTCP phasesprecipitationPrecipitation occurs until a constant fraction is reached after 100 h. High-resolution X-ray diffractionX-ray diffraction experiments conducted at room temperature revealed that the lattice parameterLattice parameter of the γ phase decreases with increasing exposure time and reaches, like the TCP phaseTCP phases fraction, a kind of plateau after long aging durations. In contrast, the lattice parameterLattice parameter of the γ′ phase hardly changes throughout aging, which results in a decrease of the initial γ/γ′ lattice misfitLattice misfit from about −1% to a plateau of about −0.45% after 1000 h. Comparison of thermodynamic and lattice parameterLattice parameter calculations with the experimentally determined values revealed that the depletionDepletion of the main TCP phaseTCP phases-forming elements Re, W, and Mo associated with the ongoing TCP phaseTCP phases formation is the main reason for this behavior. It is also shown that the effect of both stress relaxationStress relaxation and TCP phaseTCP phasesprecipitationPrecipitation results in a reduction of the tetragonal distortion and coherency stresses in the γ matrix channels.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Lattice misfit; Lattice parameter; Single crystal Ni-base superalloy; TCP phases; X-ray diffraction